The effect of weather uncertainty on the financial risk of green electricity producers under various renewable policies - Stephan Nagl (Institute of Energy Economics at the University of Cologne (EWI), 2013)
In recent years, many countries have implemented policies to incentivize renewable power generation. In this paper, we analyze the variance in profits of renewable-based electricity producers due to weather uncertainty under a `feed-in tariff policy, a fixed bonus' incentive and a `renewable quota' obligation. In a first step, we discuss the price effects of fluctuations in the feed-in from renewables and their impact on the risk for green electricity producers. In a second step, we numerically solve the problem by applying a spatial stochastic equilibrium model to the European electricity market. The simulation results allow us to discuss the variance in profits under the different renewable support mechanisms and how different technologies are affected by weather uncertainty. The analysis suggests that wind producers benefit from market integration, whereas producers from biomass and solar plants face a larger variance in profits. Furthermore, the simulation indicates that highly volatile green certificate prices occur when introducing a renewable quota obligation without the option of banking and borrowing. Thus, all renewable producers face a higher variance in profits, as the price effect of weather uncertainty on green certificates overcompensates the negatively correlated fluctuations in production and prices.
Keywords: C61; L50; Q40; 330; RES-E policy; financial risk; mixed complementarity problem